2020
DOI: 10.3390/su122310138
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Mining in the Didactic Process—MEITIM Project as an Opportunity to Increase the Attractiveness of Mining Courses (A Case Study of Poland)

Abstract: Mining has been embedded in the public consciousness as a dirty, non-innovative, outdated and environmentally harmful industry. Proper education, especially the academic one, becomes crucial to successfully change this image. This article depicts the initial assumptions of the international project Master in Entrepreneurship, Innovation and Technology Integration in Mining (MEITIM), co-financed by EIT Raw Materials, that aims to diagnose the current state of Polish higher education in the field of mining at, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The article answers the steps to be taken to increase the attractiveness of the courses at WUST. As demonstrated by the statistics published in the paper of Adach et al [12], a change in the Faculty's teaching offer is necessary, because since the academic year 2017/2018 a significant decrease in the number of graduates of the course in mining and geology has been noted. It has been shown that there is a link between the condition of the mining industry in Poland, its reputation and the number of people who want to study in this field.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The article answers the steps to be taken to increase the attractiveness of the courses at WUST. As demonstrated by the statistics published in the paper of Adach et al [12], a change in the Faculty's teaching offer is necessary, because since the academic year 2017/2018 a significant decrease in the number of graduates of the course in mining and geology has been noted. It has been shown that there is a link between the condition of the mining industry in Poland, its reputation and the number of people who want to study in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Having the experience from previously mentioned projects and analysing the newest reports on future mining, the authors realized that the minerals industry is facing a changing talent landscape [12], with digitization necessitating new skillsets, that technology cycles are getting shorter and shorter transmitting pressure in the need of trained workforce, and that mining companies need to ensure that their boards and staffs are properly constituted to support the transformations which the sector is currently undergoing, including fluency in such areas as technology, integration, systems security, and cybersecurity.…”
Section: Meitim Projectmentioning
confidence: 99%
See 2 more Smart Citations
“…For many resource-rich nations, the role of the mining sector in catalysing innovation and supporting the achievement of the development agenda is paramount. National governments around the world continue to emphasize innovation as a critical path not only to secure their economic goals but also to ensure social progress and environmental sustainability [11]. This is increasingly relevant, as global trends continue to put pressure on governments to become more forward-looking around critical issues such as globalization, climate change, population growth, emerging economies, environmental stewardship, inequality, and social benefits.…”
Section: The Mining Industry Market Needmentioning
confidence: 99%